Leadership can be learned : clarity, connection, and results - Crosby, Gilmore (Boca Raton, FL : CRC Press, 2018)
"The premise of this book, despite all that has been written on the subject, is that leadership is poorly understood because human systems are poorly understood. Like paradigms of old, which were eventually discarded--flat earth, earth at the center of the universe, and so on - most people are trapped in a limiting paradigm of personal authority and human systems. Problems are understood as 'clashes of personality,' and blame is directed at the superficial level of individuals, groups, and structure. The result is hardly more sophisticated than a soap opera. The true root cause is overlooked, and hence perpetuated. There is a way out, clearly demonstrated, consistently replicated, and yet little known. This book clarifies that path, already blazed by pioneers such as Edwin Friedman and Organization Development pioneer, Robert P. Crosby, and guides you on that path in four sections. The first section provides a transformational leadership model, the second the theory of human systems from which that leadership model emerged, the third a deep yet practical exploration of interpersonal skills related to leadership, and the fourth and final section a practical application of the aforementioned leadership model to getting results in an organization. Leadership can be learned because although there is art to leadership there is also science. With this book, you will gain a new understanding of human systems and of how to improve yourself and improve the system you are in. High performance culture and high performance leadership are mirror images of each other. Once you grasp the principals, the key will be in your hands."--Provided by publisher.
Self-differentiated leadership -- Leadership -- Vision -- Vision is not enough -- Self-differentiated leadership and systems -- Leadership and systems thinking -- Don't chase the stray cow -- Systems thinking -- Emotional intelligence and behavioral science -- Unlocking your mind, emotions, and behavior -- Emotional intelligence crosby style -- Behavioral science - the interpersonal gap -- Leading and managing -- Stability is good -- Goal alignment -- Decision making -- Feedback, reinforcement and reprimand -- Leading from forming to high performing -- Self-differentiated leadership -- Appendix a: four key skills -- Appendix b: crosby leadership quiz -- Bibliography.
Keywords: Leadership